Early Response to Incidence of Political Violence in Nigeria: A Review of Existing Strategies - Akanji, Tajudeen Ademola; Okonkwo, Nkiruka Stella (Corpus Intellectual, 2024)
In Nigeria, a culture of political violence persists, and often causes death, displacements and infrastructural damage. Various measures were introduced by the government and other stakeholders to address political violence in Nigeria; yet, there is a growing trend of violence connected with the political system. Thus, this study examines existing early response strategies for political violence in order to evaluate their effectiveness, setbacks, and sustainability. Early response strategies are critical in preventing and/or mitigating the incidence of political violence. This study aims to accomplish three specific objectives: (i) to examine the effectiveness of existing early response strategies for political violence in Nigeria; (ii) to identify the limitations of early response strategies for political violence in Nigeria; and (iii) to inform the development of integrated early response strategies for political violence in Nigeria. This study, which is based on a thorough analysis of extant literature, relevant databases and case studies of early response strategies, concludes that although some of the strategies are innovative and adaptable, they fall short in addressing emerging trends and consequences of political violence across the country. The study therefore proposes an integrated and comprehensive early response approach for addressing root causes of political violence in the country.